Ethnic topography of Novi Sad. The heritage of nations inhabiting the city - Kwoka, Tomasz (Balcanica Posnaniensia. Acta et studia, 2018)
The article is an attempt to catalogue the most interesting traces of the presence of nations which were part of the Novi Sad community throughout the ages. From the very beginning of its existence, Novi Sad was a meeting place for different ethnic and cultural groups settling down in the city. Serbs from the surrounding countryside moved to the oldest districts of Novi Sad, Podbara, Salajka, and Rotkvarija, at the beginning of the 18th century. At the same period nations from different parts of the Habsburg Empire, such as Germans, Hungarians, Slovaks and Ruthenians brought by Habsburgs to colonize Vojvodina, moved to the city. It was the time of continuous development of Novi Sad, which became an important trading and manufacturing centre, where businesses were also run by the Jews, Armenians, Aromanians (Tzintzars), and the Greeks. The turn of the 19th and 20th centuries was marked by the strengthening of presence of the Hungarian community, which ended with the First World War. After the establishment of the Kingdom of Serbs, Croats and Slovenes (1918), the ethnic structure changed seriously with the influx of Serbs from the southern regions of the country. This trend was followed after the Second World War and most recently during the period of the so-called Yugoslav wars at the Nineties. In the meantime, under dramatic circumstances of the second World War, German and Jewish inhabitants vanished from the city.